The Application of the Values of Religious Moderation in Pesantren - Saiin, Asrizal; Radiamoda, Anwar M. (Al-Wasatiyah: Journal of Religious Moderation, 2022)
This paper discusses the actualization of religious moderation values in Islamic boarding schools. For that, the keywords of religious moderation are like tawasuth, tawazun, i’tidal, tasamuh, musawah, syura, islah, awlawiyah, tathawur wa ibtikar, and tahaddhur  in this paper is used as the basis for the actualization in Islamic boarding schools. This paper is a library research with a descriptive approach and its method, qualitative. This paper concludes that Islamic boarding schools have enormous potential to instill and foster the value of religious moderation. Islamic boarding schools and their religious studies can be used as a spiritual, moral and ethical foundation in the life of the nation and state. Therefore, the ten keywords of moderation above must be taught to students. The hope is that by introducing the ten keywords of religious moderation, students will be able to understand religion and its teachings cognitively, then practice them in their families and society.